ISLAM AND EUROPEAN FEUDALISM IN THE MID-CENTURY - Basrowi, -; Sudrajat, Ajat (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2010)
This article was aimed to study the development of European Feudalism within the Mid Century. From the existing sources, it was found that as Muslim dominated Mediterranean Sea in the 8th A.D., European economy drastically declined. Moreover, it was said that the economy was near dead. The fall of trade and commerce within the continent had pushed Europe to use land as their source of life again. It is that within this situation, the feudalism found its way. The situation in Europe was changing within the 11th century, i.e. when the trade and commerce were awakening and the markets as well as cities were reviving. Commercial growth and the reuse of currency system, in fact, affected the economy of feudalists. Their life which was represented by manor was then disturbed and declining.